جهود العلماء العثمانيين في البلاغة في القرن السادس عشر حمزة بن دُرْغوُْد الآيدينيّ أنموذجًا - Bulut, Ali (Fatih Sultan Mehmet Vakıf Üniversitesi, 2020)
يهدف هذا البحث إلى تناول جهود العلماء العثمانيين في البلاغة في القرن السادس عشر، منها الهوادي في شرح المسالك لحمزة بن درغود الآيديني. يتكون البحث بعد المدخل من ثلاثة أقسام: القسم الأول يتناول جهود العلماء العثمانيين في البلاغة في القرن السادس عشر. والقسم الثاني يتناول ترجمة حمزة بن درغود الآيديني. والقسم الثالث يتناول تعريف كتاب الهوادي في شرح المسالك لحمزة بن درغود الأيديني.

Bu makalenin amacı, Aydınlı Hamza b. Turgud el-Aydınî’nin el-Hevâdî fî Şerhi’l-Mesâlik adlı eseri çerçevesinde 16. yüzyıl Osmanlı âlimlerinin belâgatle ilgili çalışmalarının tanıtılmasıdır. Çalışma girişten sonra üç bölümden oluşmaktadır: Birinci bölümde Osmanlı âlimlerinin belâgat alanındaki çalışmalarını ele almaktadır. İkinci bölüm Hamza b. Turgud’un biyografisini incelerken üçüncü ve son bölüm ise Hamza b. Turgut’a ait el-Hevâdî fî Şerhi’l-Mesâlik adlı eserin muhtevasından bahsetmektedir.

This article aims to introduce studies of the Ottoman scholars in the science of rhetoric in 16th century under the light of Hamza b. Turgud el-Aydınî, who was one of the Ottoman rhetoricians, and his work: al-Hevâdî fî Şerh al-Masâlik. The article consists of an introduction and three parts: While the first part examines the studies of the Ottoman scholars in the science of rhetoric, the second part deals with the life and works of Hamza b. Turgud, finally the third part looks into the contents of his book.
16. Yüzyıl Osmanlı Âlimlerinin Belâgatle İlgili Çalışmaları: Hamza b. Turgud el-Aydınî Örneği
The Studies of the Ottoman Scholars in the Science of Rhetoric in 16th Century About Under the Light of Hamza b. Turgud el-Aydınî
Keywords: حمزة بن درغود; الهوادي; البلاغة; العثمانيون; Hamza b. Turgud; Hevâdî; Belâgat; Osmanlılar; Rhetoric; Ottomans